2021
DOI: 10.1038/s41598-021-01373-5
|View full text |Cite
|
Sign up to set email alerts
|

The computational analyses, molecular dynamics of fatty-acid transport mechanism to the CD36 receptor

Abstract: The transmembrane glycoprotein CD36, which is responsible of the metabolic disorders, and the elevated intake of fat induces lipid buildup, is a multifunctional scavenger receptor signaling those functions in high-affinity tissue uptake of long-chain fatty acids. In this study, we used series of molecular dynamics simulations of the wild type and mutants types K164A CD36 protein interacting with one palmitic acid (PLM) besides simulations of the wild type interacting with the three PLM to find out the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The small Rg values are harmonious to a tighter packing of atoms or vice versa. Throughout the simulation, (Figure 2C) the Mpro and other Mpro‐Peptide complexes exhibited almost similar type of unimodal violin plots in terms of Rg values holding discrete average values 68 . The Mpro‐DRAMP01342 took a sudden upward direction reaching up to 22.75 Å at 48 ns and then fluctuated a bit till 53 ns which suggested that the complex showed a weak structural compaction initially.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The small Rg values are harmonious to a tighter packing of atoms or vice versa. Throughout the simulation, (Figure 2C) the Mpro and other Mpro‐Peptide complexes exhibited almost similar type of unimodal violin plots in terms of Rg values holding discrete average values 68 . The Mpro‐DRAMP01342 took a sudden upward direction reaching up to 22.75 Å at 48 ns and then fluctuated a bit till 53 ns which suggested that the complex showed a weak structural compaction initially.…”
Section: Resultsmentioning
confidence: 84%
“…Throughout the simulation, (Figure 2C ) the Mpro and other Mpro‐Peptide complexes exhibited almost similar type of unimodal violin plots in terms of Rg values holding discrete average values. 68 The Mpro‐DRAMP01342 took a sudden upward direction reaching up to 22.75 Å at 48 ns and then fluctuated a bit till 53 ns which suggested that the complex showed a weak structural compaction initially. The average Rg values for Mpro, Mpro‐DRAMP01760, Mpro‐DRAMP01808, Mpro‐DRAMP018658, Mpro‐DRAMP01737, Mpro‐DRAMP01771 were calculated as 22.1, 22.30, 22.25, 22.20, and 22.35 Å respectively from the trajectory.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations